The Role of Host‐Range Expansion and Co‐Speciation in Host–Parasite Associations With the Divergence of the Great Tit Species Complex - Xi Huang; Vincenzo A. Ellis; Yangyang Peng; Farah Ishtiaq; Haitao Wang; Wei Liang; Qiang Wu; Staffan Bensch; Lu Dong (Ecology and Evolution)
ABSTRACT During the evolution of parasites, co‐speciation and host‐range expansion are thought to play roles in establishing associations with hosts, while sorting events can lead to dissolution of those associations. To address the roles of these processes, we focus on avian haemosporidian parasites infecting hosts of the intensively studied great tit species complex. We estimated the phylogeography of lineages detected in the species complex, and quantified their transition probabilities among hosts. Lineages detected in different host species presented a strong geographical signal but did not form monophyletic groups. Yet, distributions of lineages are not merely the result of their dispersal limitations, as many lineages that infect only one focal species can be found in birds sympatric with other focal species. Besides, closely related lineages that infect the same host species reach more similar rates of infection than expected by chance. Finally, Haemoproteus and Leucocytozoon lineages infecting P. major, the most recently dispersed species, were more generalized than others, consistent with a pattern of generalist parasites expanding their host ranges by infecting newly encountered host species. Our results suggest that host–parasite associations in this system are mainly the result of sorting events and host‐range expansion of parasites, rather than co‐speciation.